Ivan Ureman - posrednik između kineske i europske znanstvene tradicije povodom 400. obljetnice njegove smrti u jubilarnoj Ignacijevoj godini (2021. - 2022.) - Borić, Marijana (2021)
U radu je prikazano djelovanje Ivana Uremana (1583.–1621.), hrvatskoga isusovca, misionara, matematičara i astronoma. Uremanov rad razmatran je iz dva aspekta. Prvi je sagledavanje Uremanova rada u sklopu razvoja znanosti njegova doba. Svojim radom na području matematike, kao i u astronomiji, Ureman se pridružuje onim učenjacima s početka novovjekovlja koji su matematičkim pristupom tražili nova znanja i uvide u spoznaju zbilje. U radu su Uremanovi znanstveni interesi i doprinosi prikazani u širem kontekstu znanstvenih prilika na prijelazu iz 16. u 17. stoljeće. Kao misionar djelovao je u razdoblju glasovitih isusovačkih misija na Dalekom istoku, pa je njegov rad također razmatran iz vidika prijenosa znanja i djelovanja prvih posrednika između kineske i europske kulturno–znanstvene tradicije.
Ivan Ureman belongs to the corpus of scholars from the beginnings of modern history who, by studying and using mathematics, marked the beginning of modern science by applying mathematics and mathematical methods in the study of nature. The application of Euclid"s method for testing scientific hypotheses — in which Ureman was an expert — would enable modern science to develop strongly and separate from philosophy, as well as to develop new autonomous fields. While the medieval scientific tradition developed a qualitative approach in researching and describing nature — following the example of Aristotle — and perceived mathematics as interacting with philosophy, in which the logical structure of mathematics was not seen as important, Ureman deviates from this tradition. His mathematical considerations were not connected with philosophy, and he used mathematics not only within its autonomous field but also in the study of astronomical phenomena, as well as in the determination of geographical coordinates and the study of magnetic declination. Confirmation of this can be found in Ureman"s scientific correspondence in which he describes his observations, mathematical data processing and the results of his research. Owing to his competence and activity, Ureman was fully integrated into the work of the famous Jesuit missions in the Far East and their role in the transfer of knowledge from the European tradition to the Chinese tradition and vice versa. He possessed a high level of theoretical and practical knowledge and skills precisely in those areas in which Chinese scholars showed a particular interest: mathematics, astronomy, the calendar, and the determination of geographical coordinates. In astronomy he carried out observations and measurements of phenomena which were the current subject of interest of the scientific community of his time. He achieved notable results in studying lunar eclipses, magnetic declination, and geographical longitude.
Bibliografske bilješke uz tekst ; bibliografija: str. 510-511.
Sažetak ; Summary.
Keywords: Astronomija -- Matematika -- Znanje; Ureman, Ivan; Isusovci; 16./17. st